Model Hewan Coba Diabetes Mellitus Yang Diinduksi Streptozocin Terhadap Kadar Gula Darah Dan Pankreas - Novalina Siregar (Majalah Kedokteran Andalas, 2021)
Objective : The purpose of this study was to determine blood sugar levels and histopathological features of the pancreas in Wistar rats (Rattus norvegicus) induced by Streptozotocin. Methods: The type of research conducted is experimental laboratory in vivo. The research design chosen was True Experimental Pre Test and Post Test Control Group Design with 24 test animals and divided into six different treatment groups. The results were analyzed using SPSS software, and for the histopathological description the rats were dissected and the pancreas was taken for preparation and then stained using the Hematoxylin Eosin (HE) method. Results: The results of this study indicate that the histopathological description of pancreatic tissue is damaged which can be seen from the occurrence of cell necrosis, cell degeneration, collections of inflammatory cell , atherosclerosis and vascular congestion are found. Blood sugar levels of rats given a combination of STZ and high-fat diet significantly increased blood sugar levels (P value < 0.05). Conclusion : There is a significant relationship between blood sugar levels and pancreatic histopathology in Wistar rats (Rattus norvegicus) induced by Streptozotocin and high-fat diet.Keywords: Diabetes mellitus; Blood Sugar Levels; Streptozotocin; Pancreas Histology